Generic typology for irrigation systems operation - Renault, D.; Godaliyadda, G.G.A. (International Water Management Institute, 1999)
This report presents a methodology for identifying the main characteristic features (constraints and opportunities) of gravity-fed irrigation systems, which influence management and operation of the system for the purpose of water delivery. It presents the development of a generic typology for improving irrigation system operations. A case study of 64 irrigation systems in Sri Lanka is presented illustrating the practical application of the proposed typology.